The Contribution of Organizational Justice and Organizational Commitment on Turnover Intention on Hotel Employees - Adhi Anggra Kusuma Putra; Anugriaty Indah Asmarany (Indonesian Psychological Research, 2024)
Basically, young hotel employees want to look for comfortable and suitable jobs, or perhaps the target load they receive exceeds the capabilities of young employees who are just starting to enter the world of work. This condition causes the emergence of turnover instruction behavior. This quantitative approach research aims to determine the influence of organizational justice and organizational commitment on turnover among hotel employees. The sample in this research was 155 hotel employees, selected using a purposive sampling technique. The organizational justice scale, the organizational commitment scale, and the turnover inventory scale were used to collect data. Data analysis was conducted out using multiple regression techniques. The results show that there is a very significant influence of organizational justice and organizational commitment on turnover intentions among hotel employees, with a contribution of 75.3% while the remaining 24.7% hotel employee is influenced by other factors, including age, education level and turnover intention.